The asthma–COPD overlap syndrome: towards a revised taxonomy of chronic airways diseases?. Issue 9 (September 2015) - Bateman, Eric D; Reddel, Helen K; van Zyl-Smit, Richard N; Agusti, Alvar
Summary Most research of treatments for airways diseases has been restricted to patients who meet standard definitions of either chronic obstructive pulmonary disease (COPD) or asthma, yet to distinguish COPD from asthma in adult patients who have clinical features of both can be challenging. Treatment guidelines provide scant advice on how such patients should be managed. With increasing recognition that asthma and COPD are heterogeneous diseases, attention has been directed to the needs of a group of patients with what is now termed asthma–COPD overlap syndrome (ACOS), particularly in view of the high morbidity in this population. This Review considers the epidemiology, mechanisms of disease, current attempts to define and diagnose ACOS, existing and potential treatment options, and new approaches to the phenotyping and taxonomy of airway diseases.